The Significance of the Five Aggregates in Understanding the Buddhist Concept of Reality - Wook, Kim Ki (University of Colombo, 2015)
The doctrine of five aggregates (pancakkhandha) should be examined comprehensively to understand its significance as follows: Consciousness (vinndna) arises every moment when sense organ, corresponding object, and attention (samannahara) meet together, forming a kind of stream (vinndnasota). When consciousness arises, the five aggregates always arise together. Therefore, the "stream of consciousness" is nothing but the "stream of the five aggregates". This "stream of the five aggregates" constitutes an individual's "subjective experiential world" (lokd) which is identified as "reality" in Buddhism. If ego-consciousness is involved in the arising of the five aggregates, they become the five aggregates of clinging (pancupadanakkhandha) in the sense that they are constructed (or conditioned) by craving (tanha), conceit (mdna), wrong view (ditthi). The "subjective experiential world" consisted of the five aggregates of clinging is dukkha for an individual who has constructed (abhisamkharoti) it as "I" or "mine", due to its inherent impermanent (anicca) nature. The constructed "world" is samkhata in the sense that it is constructed (or conditioned) by "I-ness" ignorance and craving. And the stream of the "world" is samsara. The way to end the "subjective experiential world" consisted of the five aggregates of clinging is to understand the true nature of this "world", and not to cling to it. That is, by contemplating on the five aggregates which constitute the "world" as impermanence (anicca), suffering (dukkha), and nonself (anatta), the practitioner deconstructs (visamkhara) "his world" through the process of disenchantment (nibbidd), dispassion (viraga), and liberation (vimutti). When a practitioner completely removes ignorance and craving toward "his world" consisted of the five aggregates of clinging, he achieves complete extinction of the defilements {kilesa-parinibbana) and becomes arahant. And the arahant, at his death, achieves complete extinction of the personality-factors (khandha-parinibbdna) in which the conditionality of the five aggregates itself is eliminated. ThujiTit can be observed that the five aggregates are not only a theoretical basis but also a practical basis to understand the Buddhist concept of reality.
Keywords: Five Aggregates, World, Dukkha, Nibbana